Mountains, global food prices, and food security in the developing world - Akramov, Kamiljon T.; Yu, Bingxin; Fan, Shenggen (International Food Policy Research Institute, 2010)
This study explores the differences between mountain and non-mountain countries in food security and its determinants. Econometric analysis shows that mountain regions are likely to have lower food security. The findings suggest that people in mountain countries are especially affected by external shocks such as surges in global food prices. The results of regression decomposition indicate that the disparity in food availability we observed between mountain and non-mountain countries can be explained by differences in population size, income, road density, and governance factors as well as by a differential impact of external price shocks. The direct impacts of geographic and agroecological factors seem rather limited.